Integrasi Nilai Religius dalam Layanan Konseling untuk Penguatan Kesehatan Mental - Muhamad Irsyad Ridwan (Indonesian Journal of Educational Counseling, 2026)
Mental health is influenced not only by psychological and social factors, but also by an individual's meaning in life, values, spirituality, and religious beliefs. In counseling practice, religious values can be a source of coping, resilience, hope, and identity strengthening, especially for clients who view religion as an important part of their lives. This article aims to analyze the integration of religious values in counseling services, identify relevant interventions, explain the ethical limitations of their use, and formulate practical implications for counselors and guidance and counseling teachers. This research used a descriptive qualitative approach through a narrative literature review and thematic content analysis of 23 academic sources published between 2021 and 2025. The results reveal four main themes: the role of religion and spirituality in strengthening mental health, forms of religious-spiritual interventions in counseling, ethical principles of religious value integration, and the need to strengthen counselor competence. The integration of religious values can support more holistic counseling if it is conducted based on client needs, does not impose beliefs, respects diversity, and is accompanied by professional competence. In conclusion, religious value-based counseling is not a substitute for a scientific psychological approach, but can be a culturally relevant and meaningful supporting component for clients.